Difference between revisions of "1975 AHSME Problems/Problem 27"
Megaboy6679 (talk | contribs) (→Solution 1) |
Megaboy6679 (talk | contribs) (→Solution 1) |
||
Line 17: | Line 17: | ||
<cmath>p^2 + q^2 + r^2 = -1.</cmath> | <cmath>p^2 + q^2 + r^2 = -1.</cmath> | ||
− | Therefore, <math>p^3 + q^3 + r^3 = (p^2 + q^2 + r^2) - (p + q + r) + 6 = (-1) - 1 + 6 = \boxed{4}</math>. The answer is <math>\text(E)</math>. | + | Therefore, <math>p^3 + q^3 + r^3 = (p^2 + q^2 + r^2) - (p + q + r) + 6 = (-1) - 1 + 6 = \boxed{4}</math>. The answer is <math>\text{(E)}</math>. |
==Solution 2(Faster)== | ==Solution 2(Faster)== |
Revision as of 23:05, 18 March 2023
Problem
If and
are distinct roots of
, then
equals
Solution 1
If is a root of
, then
, or
Similarly,
, and
, so
By Vieta's formulas, ,
, and
. Squaring the equation
, we get
Subtracting
, we get
Therefore, . The answer is
.
Solution 2(Faster)
We know that . By Vieta's formulas,
,
, and
.
So if we can find
, we are done. Notice that
, so
, which means that
~pfalcon